First-Pass Contrast-Enhanced Myocardial Perfusion MRI Using a Maximum Up-Slope Parametric Map. - Chun Ruan
Magnetic resonance first-pass perfusion imaging offers a noninvasive method for the rapid, accurate, and reproducible assessment of cardiac function without ionizing radiation. Quantitative or semiquantitative analysis of changes in signal intensity (SI) over the whole image sequence yields a more efficient analysis than direct visual inspection. In this paper, a method to generate maximum up-slope myocardial perfusion maps is presented. The maximum up-slope is defined by comparison of the SI variations using frame-to-frame analysis. A map of first-pass transit of the contrast agent is constructed pixel by pixel using a linear curve fitting model. The proposed method was evaluated using data from eight subjects. The data from the parametric maps agreed well with those obtained from traditional, manually derived region-of-interest methods as shown through ANOVA. The straightforward implementation and increase in image analysis efficiency resulting from this method suggests that it may be useful for clinical practice
Keywords: ANOVA; Cardiac function; Contrast agent; First-pass contrast-enhanced myocardial perfusion MRI; Frame-to-frame analysis; Image analysis efficiency; Linear curve fitting model; Maximum up-slope parametric map; Myocardial perfusion maps; Perfusion imaging; Quantitative analysis; Region-of-interest method; Semiquantitative analysis; Signal intensity; Stress test; Whole image sequence